Research status of dietary nursing intervention of hyperphosphatemia in hemodialysis patients (血液透析患者高磷血症饮食护理干预的研究现状) - WANG Liwei (王丽伟); LIU Lin (刘玲); YANG Yufei (杨寓斐); E Haiyan (鄂海燕); TANG Ling (唐玲) (中西医结合护理)
Hemodialysis patients are prone to hyperphosphatemia in the process of disease progression, which seriously reduce the patient’s quality of life. In clinical treatment and nursing, dietary nursing intervention can improve the prevention awareness of hyperphosphatemia in patients and their families, improve the level of blood phosphorus and nutritional status of patients, reduce the incidence of hyperphosphatemia in hemodialysis patients, and improve their quality of life under a scientific and reasonable diet planning. The purpose of this paper is to summarize the dietary nursing intervention of hyperphosphatemia in hemodialysis patients, summarize the dietary nursing intervention measures, and provide beneficial guidance for the practice of dietary nursing. (血液透析(HD)患者并发高磷血症, 严重影响其生活质量, 通过饮食护理干预可提高HD高磷血症患者及其家属的疾病相关预防意识, 使患者在科学、合理的饮食规划下, 改善血磷水平与营养状况, 提高患者生活与生存质量。本文旨在通过对HD高磷血症患者的饮食护理干预进行综述, 总结饮食护理干预措施, 为饮食护理实践提供有益指导。)